1964
DOI: 10.1111/j.1939-0025.1964.tb02240.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-visual integration in normal and retarded readers.

Abstract: In a study of the relation of auditory‐visual integration in a total population sample of retarded readers, they were found to be significantly less able integrators than normal readers are. The findings were interpreted as indicating that defects in auditory‐visual integration contribute to reading incompetence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
3

Year Published

1968
1968
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(92 citation statements)
references
References 5 publications
5
83
1
3
Order By: Relevance
“…He intuited that this lag would impair their ability to represent the same information in two sensory-based systems, as exemplified in learning to read. Initial support for this theory was provided by Birch and Belmont (1964), who observed that poor readers performed below the level of normal readers in matching auditorily presented rhythmic patterns with visual representations of those patterns. Because this task confounds crossmodal transfer with working memory and verbal coding ability, Vellutino and his associates (Vellutino, 1979(Vellutino, , 1987Vellutino & Scanlon, 1982) conducted a series of studies that compared poor and normal readers on both intramodal (visual-visual; auditory-auditory) and intermodal (visual-auditory) non-verbal learning tasks that minimized the influence of verbal coding ability.…”
Section: Deficits In General Learning Abilitiesmentioning
confidence: 99%
“…He intuited that this lag would impair their ability to represent the same information in two sensory-based systems, as exemplified in learning to read. Initial support for this theory was provided by Birch and Belmont (1964), who observed that poor readers performed below the level of normal readers in matching auditorily presented rhythmic patterns with visual representations of those patterns. Because this task confounds crossmodal transfer with working memory and verbal coding ability, Vellutino and his associates (Vellutino, 1979(Vellutino, , 1987Vellutino & Scanlon, 1982) conducted a series of studies that compared poor and normal readers on both intramodal (visual-visual; auditory-auditory) and intermodal (visual-auditory) non-verbal learning tasks that minimized the influence of verbal coding ability.…”
Section: Deficits In General Learning Abilitiesmentioning
confidence: 99%
“…Rather than indicating failure of integration between vision and audition, the results imply some inability to hold auditory signals in short-term memory (STM). Birch and Belmont (1964) argued against an explanation of AV failures in terms of STM since they found that memory span for auditorily presented digits was not associa ted with AV matching. However, they did not examine STM for auditory patterns.…”
Section: Results Smentioning
confidence: 99%
“…According to the theory of auditory deficit the difficulty in perceiving and discriminating speech sounds results in difficulty to build mental representations that are important to the association between letters and sounds (Banai & Kraus, 2007;Birch & Belmont, 1964).…”
Section: Auditory Deficit Theorymentioning
confidence: 99%